Oxidative bioconversion of ω-fatty acid from giant snakehead fish oil - Omar, Muhammad Nor; Othman, Siti Fairuz Che; Yusoff , Nur Shahidatul Ahlam Md; Zainuddin, Aziyah; Talib, Hasan Mohamad; Yunus, Kamaruzzaman (2009)
Studies on bioconversion of ω-fatty acids in giant snakehead and mudskipper fish oil were carried out using guinea pig lung homogenate. The fish oils were incubated aerobically at 37oC in phosphate buffer solution with the addition of guinea pig lung homogenate. After incubation it was found that ca. 72-76% of arachidonic acid has been converted to the prostaglandin metabolite. The fatty acid constituents in fish oil were analysed by GC-MS after the acids have been methylated.